PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN SISWI TENTANG PENCEGAHAN KANKER SERVIKS DI SMA NEGERI 1 MANADO - Pondaag, Cheren Christine; Wungouw, Herlina; Onibala, Franly (Universitas Sam Ratulangi)
Abstract: Cervical cancer is a malignant tumor growing inside the uterus or the cervix. Cervical cancer occuring the uterine cervix, an area reproductive organs in a woman who was the entrance to the uterus and positioned between the womb (uterus) with coitus (vagina). Health Education is the process of change behavior that dynamic, where such change is not just about the process of the transfer of material or the theory of a person to another person and neither set of procedures, but the changes occur awareness of within individual, group, or society own. This purpose to know the effect of health education on the level of student knowledge about cervical cancer prevention in SMA Negeri 1 Manado. The study design is Pre-Experimental design with one group pre-post test to assess the effect of health education on the level of student knowledge . The sample in this study that is numbered 100 students of SMA Negeri 1 Manado who have met the criteria for inclusion or exclusion criteria using purposive sampling technique. Analysis of the test data using Wilcoxon test using SPSS version 16. The Conclusion, there are significant influence between health education on the level knowledge about cervical cancer pervention with significant values 0,000. Keywords: Health education, level of knowledge, cervical cancer Abstrak: Kanker leher rahim (kankerÂ serviks) adalah tumor ganas yang tumbuh di dalam leher rahim atau serviks. Kanker serviks terjadi pada serviks uterus, suatu daerah organ reproduksi pada wanita yang merupakan pintu masuk ke rahim dan terletak antara rahim (uterus) dengan liang senggama (vagina). Pendidikan Kesehatan adalah proses perubahan perilaku yang dinamis, dimana perubahan tersebut bukan sekedar proses transfer materi/teori dari seseorang ke orang lain dan bukan pula seperangkat prosedur, akan tatapi perubahan tersebut terjadi adanya kesadaran dari dalam diri individu, kelompok, atau masyarakat sendiri. Tujuan Penelitian ini mengetahui pengaruh pendidikan kesehatan terhadap tingkat pengetahuan siswi tentang pencegahan kanker serviks di SMA Negeri 1 Manado. Desain penelitian ini bersifat Pra-Eksperimental dengan Design one group pre-post test untuk menilai pengaruh p